Kewenangan Memeriksa dan Mengadili Pengadilan Militer dalam Penyelesaian Tindak Pidana Umum yang Dilakukan oleh Anggota Militer - Adelia Kartika Nur Huda; Saiful Abdullah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The TNI as a means of defense of the Unitary State of the Republic of Indonesia has a noble task. Even though it has a noble task, the TNI is still the same as society in general which has the possibility of committing criminal acts. In practice, TNI who commit criminal acts will be investigated and tried in a Military Court. It turns out that several laws and regulations relating to the authority of the Military Court contain conflicts between one law and another law. The authority to examine and adjudicate courts within the Military justice environment in resolving general crimes committed by the TNI as stated in Article 3 paragraph (4a) of MPR Decree Number VII/MPR/2000 jo. Article 65 Paragraph (2) of Law of the Republic of Indonesia Number 34 of 2004 concerning the Indonesian National Army is apparently different from the authority of military justice contained in Law no. 31 of 1997 regarding Military Justice. In order to answer this question, research was conducted, as well as to provide an explanation regarding the resolution of general crimes committed by the TNI. This research is normative research, using a statutory approach and a conceptual approach. The research results found that the resolution of general crimes committed by the TNI was still carried out in the Military Court, referring to the legal principle of lex specialis derogate legi generali. The resolution of general crimes committed by the TNI is carried out through legal trials, consisting of the stages of investigation, prosecution, examination and proof, and the execution stage.